Fluorescent annulated imidazo[4, 5-c]isoquinolines via a GBB-3CR/imidoylation sequence – DNA-interactions in pUC-19 gel electrophoresis mobility shift assay. Issue 17 (14th April 2022) - Stahlberger, M.; Steinlein, O.; Adam, C. R.; Rotter, M.; Hohmann, J.; Nieger, M.; Köberle, B.; Bräse, S.
Abstract : Modular, sequential synthetic route involving a GBB-3CR and an imidoylative Hartwig–Buchwald amination towards fluorescent polyheterocycles. Investigation of DNA-interactions in a pUC-plasmid electrophoresis mobility shift assay. Abstract : Herein we report the development of a sequential synthesis route towards annulated imidazo[4, 5- c ]isoquinolines comprising a GBB-3CR, followed by an intramolecular imidoylative cyclisation. X-Ray crystallography revealed a flat 3D structure of the obtained polyheterocycles. Thus, we evaluated their interactions with double-stranded DNA by establishing a pUC-19 plasmid-based gel electrophoresis mobility shift assay, revealing a stabilising effect on ds-DNA against strand-break inducing conditions.